PERANCANGAN LAYANAN INTERNET RADIO UNTUK RADIO KONVENSIONAL (Studi Kasus Radio Konvensional di Kota Bandung) - Sindu Prawito, Ponsen; Fachrurrizal, Afdan (Politeknik Dharma Patria Kebumen, 2019)
The design of internet radio services for conventional radio, especially in the city of Bandung was made, because at this time many new services have sprung up with various innovations that can create new markets and can also